A cross examination of science and mathematics teachers’ perceptions, practices and constraints while doing teaching thinking across subject matter in selected primary schools in Malaysia and Saudi Arabia - Abd Hamid, Siti Rafiah; Al Habib, Ne'ma (2011)
This paper is intended to ascertain mathematics and science teachers’ perceptions, practices and constraints encountered while conducting teaching thinking (creative and critical thinking skills (Kemahiran Berfikir Kritis Kreatif - KBKK) across science and mathematics subjects in 7 primary schools in the West Coast of Malaysia (214 teachers) and 11 primary schools in Saudi Arabia. Teachers at the respective teacher training colleges in the 7 primary schools in Malaysia have attended teaching thinking curriculum and similarly teachers in the 11 schools (100 teachers) in Saudi Arabia have undergone similar training and curriculum innovation. Among the objectives of this paper are (1) to examine the teachers’ perceptions towards teaching thinking, (2) to ascertain the nature and level of teachers’ practices of teaching thinking across science and mathematics subjects and (3) to identify any forms of constraints encountered by the teachers while doing teaching thinking, (4) to gauge teachers’ readiness level with respect to practice of teaching thinking in the two countries namely Malaysia and Saudi Arabia. Data analysis was executed by employing SPSS 14.0 for Windows. Descriptive statistics was utilized to gauge the percentages of teachers’ perceptions, practices and constraints. Inferential statistics namely multiple regression analysis (MRA) was employed to ascertain predictors of teachers’ teaching thinking readiness. Findings from this study indicated that 81.1% of the teachers in Malaysia and 85.6% of the teachers in Saudi Arabia have positive perceptions about the importance of inculcating thinking skills across mathematics and science subjects. As for practice of teaching thinking, 84.2% of the teachers in Malaysia and 90.6% of the teachers in Saudi Arabia inculcate thinking skills practically across subject contents. Interestingly, 87.9% of the teachers in Malaysia and 86.1% of the teachers in Saudi Arabia prepared diversified and conducive teaching and learning environment. Approximately 76.2% of the Malaysian teachers did not encounter much problem in executing teaching thinking in schools but 51.9% of the teachers stated that the Ministry of Education did not provide enough teaching thinking workshops for them. On the average, the Saudi Arabia teachers found that some of the teaching and learning environment were not supportive of teaching thinking skills and these were inadequate tools and equipments, books and resources, time allocation, training workshops, lack of collaboration among teachers and insufficient assessment trainings. None of the independent variables examined via simultaneous multiple regression were predictors of the Malaysian and Saudi Arabia’s teachers’ teaching thinking readiness.